2021
DOI: 10.3390/jcm10040564
|View full text |Cite
|
Sign up to set email alerts
|

Hemoadsorption during Cardiopulmonary Bypass in Patients with Endocarditis Undergoing Valve Surgery: A Retrospective Single-Center Study

Abstract: Background: Aim of this study was to evaluate the outcomes of endocarditis patients undergoing valve surgery with the Cytosorb® hemoadsorption (HA) device during cardiopulmonary bypass. Methods: From 2009 until 2019, 241 patients had undergone valve surgery due to endocarditis at the Department of Cardiac Surgery, University Hospital of Basel. We compared patients who received HA during surgery (n = 41) versus patients without HA (n = 200), after applying inverse probability of treatment weighting. Results: In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 39 publications
2
30
1
1
Order By: Relevance
“…Out of the 163 clinical articles available in PubMed, 58 were identified that mentioned "catecholamines and/or vasopressors". In total, 25 papers were excluded; 12 because of non-comparability of the measurement scales [25][26][27][28][29][30][31][32][33][34][35][36]; 4 because the type and dose of vasopressors were not specified [37][38][39][40]; 1 that reported combined norepinephrine and epinephrine doses [41]; 1 that only reported on patients that had survived [42]; and 7 where there were no measurements pre-and post-adsorber use in the same patient [43][44][45][46][47][48][49]. The remaining 33 articles were summarized without considering different study designs or duration of treatment.…”
Section: Resultsmentioning
confidence: 99%
“…Out of the 163 clinical articles available in PubMed, 58 were identified that mentioned "catecholamines and/or vasopressors". In total, 25 papers were excluded; 12 because of non-comparability of the measurement scales [25][26][27][28][29][30][31][32][33][34][35][36]; 4 because the type and dose of vasopressors were not specified [37][38][39][40]; 1 that reported combined norepinephrine and epinephrine doses [41]; 1 that only reported on patients that had survived [42]; and 7 where there were no measurements pre-and post-adsorber use in the same patient [43][44][45][46][47][48][49]. The remaining 33 articles were summarized without considering different study designs or duration of treatment.…”
Section: Resultsmentioning
confidence: 99%
“…The valve surgery mentioned in the above elective heart surgery did not indicate whether they were performed for infective endocarditis or for other reasons, and one study [ 70 ] even directly excluded patients with infective endocarditis. There were five studies involving only patients with infective endocarditis, including one RCT [ 77 ], two retrospective studies [ 78 , 79 ], and two case series [ 80 , 81 ].…”
Section: Evidence For the Application Of Cytosorb During Cpb Surgerymentioning
confidence: 99%
“…Neither of the two retrospective studies could obtain cytokine values, but according to the analysis of infection indicators, Haidari et al [ 78 ] found that there was no significant difference among CRP, PCT, and WBC levels, but the recovery rate of these three parameters was significantly accelerated in the hemadsorption group. Santer et al [ 79 ] found that the WBC counts of patients treated with hemadsorption decreased significantly in the first five days after operation. The other two case series did not focus on this outcome.…”
Section: Evidence For the Application Of Cytosorb During Cpb Surgerymentioning
confidence: 99%
See 1 more Smart Citation
“…Of note, more recent studies have found no clinical benefits of CytoSorb ® HA therapy in patients with infective endocarditis undergoing mitral and aortic valve surgery. 25,26 Further, CytoSorb ® HA has been suggested to reduce plasma-free hemoglobin during prolonged CPB runs, 27 to remove bilirubin in cardiac surgery patients with hepatic failure, 28 and to rapidly remove non-dialyzable drugs with a high degree of protein binding from blood in vivo. 29 In addition, CytoSorb ® HA might remove several anticoagulant drugs such as ticagrelor and DOACs including rivaroxaban, apixaban, and edoxaban while preserving coagulation factors and proteins.…”
Section: Emergency Cardiac Surgerymentioning
confidence: 99%